Policy Myopia and Labour Market Institutions - Claudio Lucifora; Simone Moriconi (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2014)
In the public debate, poor employment performance has often been associated with the existence of extensive labour market regulations and a lack of commitment to far- sighted public policies. This paper investigates the relation between policy myopia and labour market institutions. We develop a theoretical model in which policy myopia leads an incumbent government to choose institutions that allow the creation of rents in the labour market and reduce resources available to public goods provision and social expenditure. We test these predictions empirically using panel data for 21 OECD countries for the period 19852006. We show that policy myopia is associated with more regulated labour markets, lower unemployment benefit replacement rates, and smaller tax wedges on labour.
Keywords: J64; J88; H11; 330; Policy myopia; public good provision; labour market institutions